2001
DOI: 10.1128/jvi.75.11.5381-5384.2001
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Analysis of Natural Variants of the Multimerization Region of Epstein-Barr Virus Lytic-Switch Protein BZLF1

Abstract: BZLF1 plays a key role in the induction of Epstein-Barr virus (EBV) replication. On the basis of limited sequence homology and mutagenesis experiments, BZLF1 has been described as a member of the bZip family of transcription factors, but this prospect has not been rigorously tested to date. Here, we present biophysical analysis of the multimerization domain of BZLF1, from three natural variants of EBV, and demonstrate for the first time that the region between amino acids 196 and 227 is sufficient to direct fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 29 publications
(22 reference statements)
1
30
0
Order By: Relevance
“…Zta interacts with a series of related DNA-binding sites termed Zta-response elements (ZREs). Recently, it has been demonstrated that the dimerization domain of Zta folds as a coiled-coil, although the strength of the interaction is much weaker than that of other bZIP proteins (Hicks et al, 2001). The mechanism by which Zta achieves stability as a dimer awaits further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Zta interacts with a series of related DNA-binding sites termed Zta-response elements (ZREs). Recently, it has been demonstrated that the dimerization domain of Zta folds as a coiled-coil, although the strength of the interaction is much weaker than that of other bZIP proteins (Hicks et al, 2001). The mechanism by which Zta achieves stability as a dimer awaits further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…We questioned whether this occurs by using two biophysical approaches. A synthetic peptide was generated that was equivalent to the region of Zta that we had previously shown to fold as a coiled coil in vitro (16). The propensity of the K-bZIP peptide to fold as an ␣-helix was assessed first using circular dichroism (CD) spectroscopy.…”
mentioning
confidence: 99%
“…By analogy with other members of the bZIP family, the multimerization interface of ZEBRA has been predicted to fold through a coiled-coil structure (Sinclair & Farrell 1992). Biophysical evidence that this prediction holds true was recently provided (Hicks et al 2001). …”
Section: Zebra Structurementioning
confidence: 99%